Ground penetrating radar in temperate ice: englacial water inclusions as limiting factor for data interpretation - Ogier, Christophe; id_orcid:0 000-0002-5526-6071; van Manen, Dirk-Jan; Maurer, Hansruedi; Räss, Ludovic; id_orcid:0 000-0002-1136-899X; Hertrich, Marian; id_orcid:0 000-0001-9525-4609; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570 (Cambridge University Press, 2023)
ISSN:0022-1430 ISSN:1727-5652